Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Chapters R-4 - Cumulative Review Exercises - Page 322: 22



Work Step by Step

Substituting $x=3$ in the given function $g(x)=-x^2-2x+6,$ then $g(3)$ evaluates to \begin{array}{l}\require{cancel} g(3)=-(3)^2-2(3)+6 \\\\ g(3)=-9-6+6 \\\\ g(3)=-9 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.